2012
DOI: 10.1177/0748233712446730
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Yucca schidigera supplementation reduces arsenic-induced oxidative stress in Swiss albino mice

Abstract: The aim of this study was to clarify the effects of dietary supplementation with Yucca schidigera (Ys) on lipid peroxidation (LPO), antioxidant activity, some biochemical parameters and histopathological changes in arsenic-exposed mice. Forty Swiss albino male mice were divided into five equal groups. Group I (control group) was given normal diet and tap water for 28 days. Group II (arsenic group) was given normal diet and 100 mg/L arsenic along with drinking water for 28 days. Groups III-V were given three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…Many researchers have demonstrated that in vivo arsenic exposure affected the sperm function (Sarkar et al, 2003;Momeni & Eskandari, 2012). Arsenic causes oxidative stress on male reproductive system (Tandon et al, 2012;Ince et al, 2013), as well as increases levels of MDA, decreases the GSH levels and activities of antioxidant enzymes such as SOD and CAT (Chang et al, 2007;Manna et al, 2008;Ince et al, 2013). The enhanced production of tissue LPO observed in this study agrees with the results of other studies.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Many researchers have demonstrated that in vivo arsenic exposure affected the sperm function (Sarkar et al, 2003;Momeni & Eskandari, 2012). Arsenic causes oxidative stress on male reproductive system (Tandon et al, 2012;Ince et al, 2013), as well as increases levels of MDA, decreases the GSH levels and activities of antioxidant enzymes such as SOD and CAT (Chang et al, 2007;Manna et al, 2008;Ince et al, 2013). The enhanced production of tissue LPO observed in this study agrees with the results of other studies.…”
Section: Discussionsupporting
confidence: 94%
“…The control group received a standard diet and tap water, arsenic (100 mg l À1 , approximately 1/50 of oral LD 50 ) was given via drinking water (Glattre et al, 1995;Ince et al, 2013) to experimental groups except control group, and PD was orally given to the other groups at dose of 50, 100 and 200 mg kg À1 during 60 days. At the end of the experiment, animals were anaesthetised with light ether and then sacrificed.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, arsenic increased MDA levels of tissues and caused LPO in rats. The findings are similar to many other studies . These studies show that arsenic has an important oxidant effect and increases the formation of free radicals and decreases the efficiency of antioxidants, thus significantly increasing MDA levels .…”
Section: Discussionsupporting
confidence: 91%
“…Glutathion peroxidase (GPx) and catalase (CAT) activities were increased with YSE supplementation in rabbits (Ashour, Alagawany, Reda, & Abd El‐Hac, ). Dietary supplementation of YSE, in a dose‐dependent manner, ameliorated arsenic‐induced oxidative stress, lipid peroxidation and increased activities of antioxidant enzymes in mice (Ince, Kucukkurt, Turkmen, Demirel, & Sever, ). YSE can also compensate the toxic effects of lead‐induced oxidative stress in quails (Alagawany et al, ; Farag et al, ).…”
Section: Introductionmentioning
confidence: 99%